Shiva and Parvathi - 107 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in This statue is broken at the hands making it difficult to identify the deity. However, we can infer that the right front hand of Shiva is holding the damaru - a small drum - one of Shiva's signature items. And the back left hand could be holding the Trishula.